Successful Visual Rehabilitation Following Pars Plana Vitrectomy and Endolaser in a Patient with Severe Vitreous Hemorrhage due to Proliferative Diabetic Retinopathy - Ramzi Amin; Rafika (HM Publisher, 2024)
Proliferative diabetic retinopathy (PDR) represents an advanced stage of diabetic eye disease, frequently leading to severe visual impairment through complications such as vitreous hemorrhage (VH). Dense VH significantly obstructs vision and often requires surgical intervention. Pars plana vitrectomy (PPV) coupled with endolaser photocoagulation serves as a critical treatment modality, aiming to clear the hemorrhage, remove tractional elements, and manage the underlying ischemic drive of PDR. This report documents a case demonstrating significant visual recovery after this intervention. A 53-year-old male, diagnosed with type 2 diabetes mellitus 6 years prior and under medical control, presented with a one-month history of sudden, severe vision loss in his right eye (OD). His best-corrected visual acuity (BCVA) was profoundly reduced to 1/300 OD, while the left eye (OS) measured 6/15. Clinical examination revealed dense VH OD, preventing detailed funduscopic assessment. The fellow eye OS exhibited features consistent with high-risk PDR. The patient underwent a 23-gauge PPV, including core vitrectomy and extensive pan-retinal endolaser photocoagulation OD, performed under general anesthesia. Postoperatively, the vitreous clarity was restored, and a remarkable improvement in BCVA OD to 6/7.5 was achieved by the three-week follow-up visit. In conclusion, timely surgical management utilizing PPV with endolaser photocoagulation was effective in resolving dense VH secondary to PDR in this patient, culminating in substantial visual rehabilitation